Water Stability of Silane Coupling Agent Modified Foamed Asphalt Mixtures in the Monsoon Freezing Zone - Guo, Shengjie; Liu, Na; He, Wenan; Xiang, Zijun (Scientific Journal of Technology, 2025)
In order to evaluate the effect of silane coupling agents on the water stability of foamed asphalt mixtures,In this paper, split tests were conducted to investigate the water stability of matrix asphalt (AH90) mixes, foamed asphalt (FAH90) mixes and silane coupling agent modified foamed asphalt (MFAH90) mixes after salt-freeze-thaw cycles.The results show that the split tensile strength ratios of all types of asphalt mixtures gradually decrease with the increase in the number of salt-freeze-thaw cycles.The TSR of MFAH90 exceeded that of AH90, indicating that the addition of silane coupling agent improved the water stability of the foamed asphalt mixture and compensated for the lack of water stability of the foam asphalt mixture.